The Mechanosensory Role of Osteocytes and Implications for Bone Health and Disease States - Choi, Jung Un Ally; Kijas, Amanda W.; Lauko, Jan; Rowan, Alan E. (Frontiers in Cell and Developmental Biology, 2022)
Bone homeostasis is in dynamic equilibrium between bone-forming osteoblasts and bone-resorbing osteoclasts. This process is precisely controlled by the most abundant and mechanosensitive bone cells, osteocytes, that reside individually, within chambers of hard impermeable hydroxyapatite bone matrix. Recent studies have unveiled more functional roles of osteocytes in directly contributing to local matrix regulation as well as systemic roles through endocrine functions by communicating with distant organs such as the kidney. Osteocyte function is governed largely by both biochemical signaling and the mechanical stimuli that bone experiences. Constant mechanical stimulation is required to maintain bone health and in contrast, aging and reduced level of loading lead to bone loss and the chronic bone-loss disease, osteoporosis. The underlying mechanisms that modulate these mechanotransduction responses of the key regulatory bone cell type, osteocytes, are becoming more important than ever before. To date, both in vivo and in vitro approaches have been established to answer important questions such as effect of mechanical stimuli type, the mechanosensors involved, and the mechanosensitive signaling pathways in osteocytes. However, our understanding of osteocyte mechanotransduction has been limited due to technical challenges of working with these cells that are individually embedded within the hard hydroxyapatite bone matrix. This review highlights the current knowledge of osteocyte functions in maintaining bone health and the key mechanoregulatory pathways of these most mechanoresponsive bone cells. Finally, we elaborate on potential therapeutic opportunities by targeting osteocyte-directed signaling as well as existing treatments.